RPL32 Promotes Lung Cancer Progression by Facilitating p53 Degradation - Jiansheng Xie; Wei Zhang; Xiaojing Liang; Chong Shuai; Yubin Zhou; Hongming Pan; Yunhai Yang; Weidong Han (Elsevier, 2020)
Lung cancer is the leading cause of cancer death worldwide, and the overall survival rate of advanced lung cancer patients is unsatisfactory. Ribosomal proteins (RPs) play important roles in carcinogenesis. However, the role of RPL32 in lung cancer has not been demonstrated. Here, we report that RPL32 is aberrantly, highly expressed in lung cancer tissues and that the overexpression of RPL32 is correlated with the poor prognosis of these patients. RPL32 silencing significantly inhibited the proliferation of lung cancer cells, with an observed p53 accumulation and cell-cycle arrest. Mechanistically, knockdown of RPL32 resulted in ribosomal stress and affected rRNA maturation. RPL5 and RPL11 sensed stress and translocated from the nucleus to the nucleoplasm, where they bound to murine double minute 2 (MDM2), an important p53 E3 ubiquitin ligase, which resulted in p53 accumulation and inhibition of cancer cell proliferation. As lung cancer cells usually express high levels of Toll-like receptor 9 (TLR9), we conjugated RPL32 small interfering RNA (siRNA) to the TLR9 ligand CpG to generate CpG-RPL32 siRNA, which could stabilize and guide RPL32 siRNA to lung cancer cells. Excitingly, CpG-RPL32 siRNA displayed strong anticancer abilities in lung cancer xenografts. Therefore, RPL32 is expected to be a potential target for lung cancer treatment.